2018
DOI: 10.1016/j.nefro.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Value of immunohistochemical expression of podocalyxin in active lupus nephritis

Abstract: Podocyte loss indicated by podocalyxin immunohistochemical expression reflects the degree of activity and severity of LN and the degree of podocyte effacement by E/M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Recent studies revealed that podocyte loss indicated by podocalyxin immunohistochemical expression in LN renal biopsy reflects the degree of disease pathological activity and severity and the degree of podocyte effacement by electron microscope (26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that podocyte loss indicated by podocalyxin immunohistochemical expression in LN renal biopsy reflects the degree of disease pathological activity and severity and the degree of podocyte effacement by electron microscope (26).…”
Section: Discussionmentioning
confidence: 99%